A Disability Awareness Poster Contest at Bronx Community College of The City University of New York (CUNY) - Caraballo, Carmen; Miele Rodas, Julia (Disability Studies Quarterly, 2008)
The student art presented here (including detailed verbal descriptions) grows out of a disability awareness poster contest held at Bronx Community College of the City University of New York in the spring semester of 2008. Including a reproduction of a poster by student Carmen Caraballo, this brief article provides a description of the project and discusses the ways in which it offered enrichment at many levels. Specifically, by involving students, faculty, and administration in its process, the contest successfully supported an expansive awareness mission in a community which does not outwardly embrace visible disability.